1987
DOI: 10.1203/00006450-198711000-00018
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Constriction of the Ductus Arteriosus by Nonsteroidal Antiinflammatory Drugs in Near-Term and Preterm Fetal Rats

Abstract: ABSTRACT. Herein we report age differences of in vivo of the newborn were reported following maternal ingestion of a constriction of the fetal ductus arteriosus by nonsteroidal NSAID (lo), and nothing is known about ductal reactivity in antiinflammatory drugs in near-term and preterm rats. Two midtrimester to NSAIDs, which inhibit cyclooxygenase and depotent nonsteroidal antiinflammatory drugs, indomethacin creases endogenous prostaglandins. However. in rats, ductal conand flurbiprofen, were studied in preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…Previous studies in rats and humans have shown that the preterm fetal DA is less responsive to indomethacin-induced constriction, in contrast to the DA of full-term fetuses (19,20). In the current studies, we examined the effect of gestational age on indomethacin-induced fetal DA constriction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rats and humans have shown that the preterm fetal DA is less responsive to indomethacin-induced constriction, in contrast to the DA of full-term fetuses (19,20). In the current studies, we examined the effect of gestational age on indomethacin-induced fetal DA constriction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 3 mg/kg has been chosen as a dose which blocks whole body synthesis of prostaglandins (32). Because indomethacin crosses the placenta (4,33), and our fetuses would continue to have a placental circulation throughout the experiment, we treated both the ewe and fetus with 3 mg/kg of indomethacin to prevent losses across the placenta. Tyler et al (30), LeMer et al (4), and Redding et al (3 1) each used intervals of 30-45 min after administration to measure the effects of prostaglandin synthesis blockade.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that the constrictive response of the DA to indomethacin is an appropriate index of the DA differentiation [8,11,19,26]. We showed previously that the effect of indomethacin on the DA constriction was observed on days 19 2 /3 and later of gestation, and that the constrictive effect increased toward term [1].…”
Section: Discussionmentioning
confidence: 99%